Tangible And Intangible Evolution In Chinese Printmaking Artwork From 1980 To 2000 - Liu, Nan (2024)
Before 1980, printmaking was used as a tool for reproduction and propaganda due to the need for cultural dissemination and ideological propaganda in the war of resistance against japanese aggression, and the adaptation, reconstruction, and interdisciplinary integration of the language of printmaking between 1980 and 2000 ultimately accomplished the modernization of the printmaking. However, after 2000, the policy of combining art and national orientation has plunged chinese printmaking into the predicament of “modelization”. Although chinese printmaking has a glorious history of 2000 years, it has not been well explored. Therefore, this study analyzes the tangible and intangible evolution of chinese printmaking art from 1980 to 2000 in a systematic and structured way by applying iconographic and formalism theories, which precisely divide the research elements into tangible and intangible parts, and combines qualitative methods such as content analysis and thematic analysis to reveal the specific forms and laws of the evolutions that printmaking underwent during the peak of its transformation. The results of this study found that intangible evolution influence the presentation of tangible evolution, and that the most notable change in chinese printmaking art over the past 20 years has been the breakthrough of the original unified forms and painting rules under freedom of thought, the expansion of methods of expression, and the completion of the modernization of chinese printmaking.